Implementation of Ichiro Teen-Size Humanoid Robots For Supporting Autism Therapy - Muhammad Attamimi; Muhtadin Muhtadin (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
The humanoid robot is a robot which has humanlikeshapes and/or functions. For instance, a humanoid robot hasa neck that connect the head to the body, two legs to supportthe body, and has two arms on the right- and left-side of itsbody. According to the RoboCup competition, the humanoid robotcan be classified into several types based on their sizes, i.e.,kid-size, teen-size, and adult-size. In this study, we developeda teen-size humanoid robot with the aim of approaching thesize of children’s bodies with autism to facilitate the interactionsbetween the robot and the children. In general, the autism personis difficult to communicate with a normal person because there isa virtual wall that limits the world of the autism with the normalperson. As long as the wall is standing upright, communicationwill be difficult, so that inconvenience occurred on both sides.Especially in children, the process learning will be hampered ifcommunication is blocked. In many cases, the autism childrenmore actively interact and/or communicate with objects such asbooks, toys, and so forth. This motivated us to use a humanoidrobot as a mediator of interactions and/or communication withthe autism to support their therapy. Of course the choice ofhumanoid robots must also be considered both financially andfunctionally. At present there are many commercial humanoidrobots such as: NAO, Darwin-OP, and so forth. However, theprice offered is relatively expensive and also inflexible capabilitiesbecause existing hardware and software can no longer be freelydeveloped. Flexibility in hardware and software is very importantfor the implementation of a system that can be used in supportingthe therapy for autism. These facts motivated us to develop theIchiro teen-size robot. In this study, we developed a therapy forautism in the form of movement by humanoid robots such asa gymnastic movement. The movement is expected to be ableto be followed by the autism and has a positive impact ontherapy. One of the advantages of this study is being able toadd robot movement flexibly, so that the movements suggestedby psychiatrists should be able to be implemented and help tosupport the autism.Keywords: humanoid robots, RoboCup, robot's movements, therapy for children autisms.